The Role of Sensitization to Allergen in Asthma Prediction and Prevention - Moustaki, Maria; Loukou, Ioanna; Tsabouri, Sophia; Douros, Konstantinos (Frontiers in Pediatrics, 2017)
The burden of asthma in childhood is considerable worldwide, although some populations are much more affected than others. Many attempts have been made by different investigators to identify the factors that could predict asthma development or persistence in childhood. In this review, the relation between atopic sensitization as an indicator of allergy and asthma in childhood will be discussed. Cross sectional studies, carried out in different countries, failed to show any firm correlation between asthma and atopic sensitization. Birth cohort mainly of infants at high risk for asthma and case control studies showed that atopic sensitization was a risk factor for current asthma in children older than 6 years. In general, clear relations are observed mostly in afﬂuent Western countries, whereas in less afﬂuent countries the picture is more heterogeneous. For the prediction of asthma development or persistence in school age children other prerequisites should also be fulfilled such as family history of asthma and wheezing episodes at preschool age. Despite the conductance of different studies regarding the potential role of allergen avoidance for the primary prevention of childhood asthma, it does not seem that this approach is of benefit for primary prevention purposes. However the identification of children at risk for asthma is of benefit as these subjects could be provided with the best management practices and with the appropriate secondary prevention measures.